Implementation of Al-Islam and Kemuhammadiyahan (AIK) Based on Wasathiyah Islam in Muhammadiyah Higher Education (PTM) - Fauziyah Putri Meilinda; Absori (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
STAI Muhammadiyah Probolinggo carries out the Catur Darma of Higher Education policy by adding Al-Islam dan Kemuhammadiyahan as the fourth dharma. This policy is explained through the institution's mandatory course, namely Al-Islam dan Kemuhammadiyahan (AIK) which must be taken by all students, including Muslims from Muhammadiyah and non-Muhammadiyah backgrounds. This research focuses on two aspects: (1) the AIK policy at STAI Muhammadiyah Probolinggo, and (2) the implementation of the AIK policy for students with non-Muhammadiyah backgrounds. This research is qualitative, using observation, in-depth interviews and documentation. The research results show that (1) students from non-Muhammadiyah backgrounds are required to take AIK courses, with lecturers paying attention to proportions, material presented, and local context; and (2) the AIK learning model involves rules of study, which changes the doctrinal approach to a dialogical one, namely using a theory-based curriculum approachWasathiyah as the main analytical tool.